Hypertext Based E-Module Innovation (e -MHP) in Learning Islamic Religious Education - Sumarno (Kirana Publisher (KNPub), 2025)
This research began from the inability of textbooks to present the nonlinearity and complexity of Islamic religious education subject material. The purpose of this study is to find out: 1) the design of the teaching and learning process with hypertext-based e-modules; 2) the relationship of hypertext-based e-module innovation to students' cognitive flexibility; 3) the impact of hypertext-based e-module innovation on student learning achievement. The research method used in this study is mixed methods, which combines qualitative and quantitative research to understand the problem. The results of the study show that: 1) the design of the teaching and learning process with hypertext-based e-modules actualizes the actors of the teaching and learning process in an effort to build knowledge together; 2) the design of the teaching and learning process with hypertext-based e-modules increased students' cognitive flexibility by 47.7%; and 3) the design of the teaching and learning process with hypertext-based e-modules has a positive impact on student learning achievement of 0.77 sigma. Various data analyzes show that the design of the teaching and learning process with hypertext-based e-modules has received a positive response so that it can be used as a suitable auxiliary media for teachers and students.